Electronic Worksheet-Based Problem Based-Learning (PBL) Toward Problem-Solving in Science Education: Need Analysis - Indah Kristiani Siringo Ringo; Tien Aminatun; Insih Wilujeng; Sabar Nurohman (Jurnal Penelitian Pendidikan IPA, 2023)
Both teachers and students require teaching materials to assist learning. This is necessary for students to understand the course and will greatly aid understanding, Problem-solving skills are very important for students, but students feel inadequate in problem-solving skills, so there is a need for teaching materials that contain Problem-Based Learning. This study aims to analyze the need for teaching materials, especially student worksheets based on Problem-Based Learning to improve student problem-solving. This research is qualitative and quantitative. The subjects of this study were students of class VIII SMP Negeri 14 Yogyakarta. Research data were collected using a questionnaire containing 16 questions, interviews, and observations. The methods for data analysis Techniques for analyzing data include using qualitative methods to examine how curriculum, student characteristics, and learning resources are used and presenting the results in forms that may be used for descriptive statistics, such as graphs and standard tables. The results showed that: Based on interviews, questionnaires, and observations on teaching materials, student characteristics, and the curriculum used. It can be said that, on average, 79.8% of students need additional electronic-based teaching materials on the topic of additives and addictive substances, and the unavailability of teaching materials in the form of electronic worksheets based on problem-based learning.